Pengaruh Leverage, Firm Size, Dan Growth Opportunity Terhadap Earnings Response Coefficient - Marcelius Setiawan, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to analyze the effect of leverage, firm size, and growth opportunities on the earnings response coefficient. This research was conducted using 180 samples of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The sampling technique used was purposive sampling. The data in this study were calculated using the Microsoft Excel program and analyzed using the EViews version 11 program. The results of this study concluded that firm size has a positive and significant effect on the earnings response coefficient, while the leverage and growth opportunity have no significant effect on the earnings response coefficient. The implication of this research is that the size of a firm is one of the main determinants of the magnitude of the response coefficient on company reported earnings.